Plant-derived bisbenzylisoquinoline alkaloid tetrandrine prevents human podocyte injury by regulating the miR-150-5p/NPHS1 axis - Sun Yue; Yuan Chenyi; Yu Jin; Zhu Caifeng; Wei Xia; Yin Jiazhen (Open Chemistry, 2022)
Podocytes have become a crucial target for kidney disease. Tetrandrine (TET), the main active component of a Chinese medicine formula Fangji Huangqi Tang, has shown a positive effect on various renal diseases. We aimed to investigate the effect and mechanism of TET on podocytes. The targeting relationship between microRNA (miR)-150-5p and nephrosis 1 (NPHS1) was determined by a dual-luciferase reporter gene assay. Cell proliferation, migration, and apoptosis were detected by cell counting kit-8, Transwell, and flow cytometry assays, respectively. The expression of miR-150-5p and NPHS1 was detected by RT-qPCR. The levels of Nephrin, Caspase-3, Bcl-2, Bax, E-cadherin, and α-smooth muscle actin were detected by Western blot. TET prompted cell viability and inhibited migration and apoptosis of puromycin aminonucleoside-induced human podocytes (HPC) in a dose-dependent manner. miR-150-5p directly targeted NPHS1 and was upregulated in damaged HPC. TET decreased the miR-150-5p expression and increased the level of NPHS1 and Nephrin. Overexpressed miR-150-5p inhibited the expression of NPHS1 and Nephrin, and reversed the protective effects of TET on injured HPC. TET protects the biological function of HPC by suppressing the miR-150-5p/NPHS1 axis. It reveals that TET may be a potential drug and miR150-5p is a potential therapeutic target for the treatment of podocyte injury.